Efforts to increase students' interest in learning through the learning media of number cards with whole numbers in addition and subtract - Hijrah, Nurul; Hasibuan, Lily Rohanita; Julyanti, Eva (Desimal: Jurnal Matematika, 2024)
This study aims to increase students' interest in mathematics. Students can use number card learning media as an alternative method of learning integers (addition and subtraction). In mathematics, the material on integers (addition and subtraction) discusses abstract properties in mathematics. Based on this study, the study was conducted through observation of class VII students at MTs Altihadul Wathoniayah. This research takes the type of quantitative research through an experimental approach and uses a Pretest-Posttest Design. This research involves all class VII MTs Al Ittihadul Wathoniyah, both class VII-A and VII-B. However, the sample used randomly is type VII-A which consists of 30 samples used in this study to conduct tests to collect data on reasoning skills and mathematics learning outcomes. After testing with the hypothesis that the calculated value is greater than the table's t value. The results of the data show that the use of number cards in conducting research on mathematics learning media is effective in increasing students' interest in learning mathematics subjects and achieving satisfactory results.